Effects of wheat protein in milk replacers on abomasal emptying rate in calves. Issue 2 (19th July 2015) - Wittek, T.; Ernstberger, M.; Muckenhuber, M.; Flöck, M.
Summary: Diarrhoea is a condition with tremendous impact on calf health. Infectious agents play a dominant role; however, non‐infective factors may also contribute to pathogenesis of diarrhoea. One factor, the abomasal emptying rate, is mainly influenced by the composition of feed. The aim of the study was to assess the influence of different protein sources in milk replacers on abomasal emptying rate and clinical parameters. The effect of increasing age of the calves on abomasal emptying was also evaluated. The study compared abomasal emptying rates and clinical parameters in calves, which were fed either milk replacer containing only whey protein or one which partially contained wheat protein. Abomasal emptying rate was estimated by ultrasonography. Ten calves were used in the study over 18 days, and each calf was fed 3 periods of 3 days length using different milk replacers in an alternating crossover design. The abomasum was emptied significantly faster when the wheat protein containing milk replacer was fed (half‐emptying time wheat protein 49.1 ± 4.1 min, half‐emptying time milk protein 59.1 ± 7.4 min); however, clinical parameters and weight gain did not differ between the feeding regimes. Age did not significantly influence abomasal emptying rate. As milk replacers containing wheat proteins increased abomasal emptying rate, they may have a higher potential to initiate diarrhoea, especially if high volumes are fed. Thus, the feeding regimes are likely to be even more important when such milk replacers are used.